2016
DOI: 10.3389/fpls.2016.00414
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Haploids Are Preferentially Induced by CENH3-tailswap Transgenic Complementation in Maize

Abstract: Doubled haploid plants are invaluable breeding tools but many crop species are recalcitrant to available haploid induction techniques. To test if haploid inducer lines can be engineered into crops, CENH3 −/− and CENH3:RNAi lines were complemented by AcGREEN-tailswap-CENH3 or AcGREEN-CENH3 transgenes. Haploid induction rates were determined following testcrosses to wild-type plants after independently controlling for inducer parent sex and transgene zygosity. CENH3 fusion proteins were localized to centromeres … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(94 citation statements)
references
References 20 publications
7
82
3
2
Order By: Relevance
“…MiMe combined with genome elimination indeed leads to clonal offspring, as previously demonstrated in Arabidopsis [13]. However, the CENH3 manipulation used in Arabidopsis to provoke genome elimination has not been transferred in other species to date [20,[39][40][41], except in maize but with a lower frequency [42]. The frequency of genome elimination can be genetically controlled in cereals, notably in maize [43][44][45].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…MiMe combined with genome elimination indeed leads to clonal offspring, as previously demonstrated in Arabidopsis [13]. However, the CENH3 manipulation used in Arabidopsis to provoke genome elimination has not been transferred in other species to date [20,[39][40][41], except in maize but with a lower frequency [42]. The frequency of genome elimination can be genetically controlled in cereals, notably in maize [43][44][45].…”
Section: Discussionmentioning
confidence: 63%
“…The caryopses were then washed thrice in sterile distilled water. Embryos were isolated following two distinct procedures depending on the presence or absence of endosperm [42,43]. Immature embryos were plated on MS basal medium [44] supplemented with 50 g/l sucrose and 6 g/l phytagel.…”
Section: Embryo Rescuementioning
confidence: 99%
“…This approach has particular appeal as CENH3 is a conserved protein across all plant species, meaning it can potentially be applied to generate haploid inducers in any plant species. This was recently demonstrated in maize and barley, although in barley, multiple copies of CENH3 complicated the haploid induction (Karimi-Ashtiyani et al 2015; Kelliher et al 2016). …”
Section: Why Study Apomixis?mentioning
confidence: 89%
“…Recently, Kelliher et al (2016) have reported CENH3-mediated haploid production in maize. In this study, native CENH3 was silenced using RNAi approach or by transposon insertion.…”
Section: Significance Of Cenh3 In Plant Breeding a Novel Methods Of Hamentioning
confidence: 99%